125OPembrolizumab + chemotherapy for advanced G/GEJ adenocarcinoma (GC): The phase III KEYNOTE-062 study. (24th November 2019) - Chung, H C; Bang, Y-J; Tabernero, J; Van Cutsem, E; Fuchs, C S; Wyrwicz, L; Lee, K-W; Kudaba, I; Garrido, M; Castro, H; Mansoor, W; Braghiroli, M I; et al.
Abstract: Background: KEYNOTE-062 (NCT02494583) was a randomized, active-controlled study of first-line (1L) pembrolizumab (pembro) or pembro+chemotherapy vs chemotherapy (chemo) in patients (pts) with PD-L1 combined positive score ≥1 (CPS ≥1), HER2 –, advanced GC. Methods: Eligible pts were randomly assigned 1:1:1 to pembro 200 mg Q3W, pembro+chemo (cisplatin 80 mg/m 2 + 5-FU 800 mg/m 2 /d on d1-5 Q3W [or capecitabine 1000 mg/m 2 BID on d1-14 Q3W per local guidelines]) or placebo+chemo Q3W for up to 2 y. Randomization was stratified by region, disease status, and fluoropyrimidine treatment. Primary end points were OS in CPS ≥1 and CPS ≥10 for pembro+chemo vs chemo and pembro vs chemo, and PFS (RECIST v1.1; central review) in CPS ≥1 for pembro+chemo vs chemo. Secondary end point was ORR (RECIST v1.1; central review) in CPS ≥1 for pembro+chemo vs chemo. Final analysis cutoff date was March 26, 2019. Results: 763 pts (281 with CPS ≥10 tumors) were randomly assigned to pembro+chemo (n = 257), pembro (n = 256), or chemo (n = 250). Median follow-up was 11.3 mo. Pembro was noninferior to chemo for OS in CPS ≥1 per prespecified margins. Pembro prolonged OS vs chemo in CPS ≥10 (median 17.4 vs 10.8 mo; HR 0.69; 95% CI 0.49-0.97) but was not tested per analysis plan. Pembro+chemo was not superior to chemo for OS in CPS ≥1 or CPS ≥10; the trend for pembro+chemo was favorable. Pembro+chemo did not significantly prolong PFS in CPS ≥1. ORR was higher with pembro+chemo than with chemo. In pts with microsatellite instability–high tumors, median OS was not reached (pembro) vs 8.5 mo (chemo) (HR 0.29; 95% CI 0.11-0.81) and not reached (pembro+chemo) vs 8.5 mo (chemo) (HR 0.37; 95% CI 0.14-0.97). Grade 3-5 drug-related AE rates were 17% (pembro), 73% (pembro+chemo), and 69% (chemo). Conclusions: As 1L therapy for advanced GC, pembro was noninferior to chemo for OS in CPS ≥1; improvement in OS was clinically meaningful in CPS ≥10. Pembro+chemo was not superior for OS and PFS in CPS ≥1 or OS in CPS ≥10. The safety profile was more favorable for pembro than for chemo. Clinical trial identification: NCT02494583. Editorial acknowledgement: Medical writing and/or editorial assistance was provided by Traci Stuve, MA, of the ApotheCom pembrolizumab team (Yardley, PA, USA). This assistance was funded by Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Legal entity responsible for the study: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Funding: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Disclosure: H.C. Chung: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Merck-Serono; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Lilly; Honoraria (self): Foundation Medicine; Advisory / Consultancy, Research grant / Funding (institution): Taiho; Advisory / Consultancy: Celltrion; Advisory / Consultancy: Quintiles; Advisory / Consultancy: BMS; Research grant / Funding (institution): GSK; Research grant / Funding (institution): MSD; Research grant / Funding (institution): BMS-ONO. Y-J. Bang: Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Advisory / Consultancy, Research grant / Funding (institution): Genentech/Roche; Advisory / Consultancy, Research grant / Funding (institution): MSD; Advisory / Consultancy, Research grant / Funding (institution): Merck Serono; Advisory / Consultancy, Research grant / Funding (institution): Bayer; Advisory / Consultancy, Research grant / Funding (institution): BMS; Advisory / Consultancy, Research grant / Funding (institution): Eli Lilly; Advisory / Consultancy, Research grant / Funding (institution): Taiho; Advisory / Consultancy, Research grant / Funding (institution): Daiichi-Sankyo; Advisory / Consultancy, Research grant / Funding (institution): Astellas; Advisory / Consultancy, Research grant / Funding (institution): BeiGene; Advisory / Consultancy, Research grant / Funding (institution): GreenCross; Advisory / Consultancy: Samyang Biopharm; Advisory / Consultancy: Hanmi; Advisory / Consultancy: Genexine; Research grant / Funding (institution): GSK; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Boehringer Ingelheim; Research grant / Funding (institution): MacroGenics, Boston Biomedical, FivePrime, Curis, Taiho, Takeda, Ono, CKD Pharma. J. Tabernero: Advisory / Consultancy, Scientific consultancy role: Array Biopharma, AstraZeneca, Bayer, BeiGene, Boehringer Ingelheim, Chugai, Genentech, Inc., Genmab A/S, Halozyme, Imugene Limited, Inflection Biosciences Limited, Ipsen, Kura Oncology, Lilly, MSD, Menarini, Merck Serono, Merrimack, Merus, Molecular Partn. E. Van Cutsem: Advisory / Consultancy: Astellas; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution): Bayer; Advisory / Consultancy, Research grant / Funding (institution): Bristol-Myers Squibb; Advisory / Consultancy, Research grant / Funding (institution): Celgene; Advisory / Consultancy: Incyte; Advisory / Consultancy, Research grant / Funding (institution): Lilly; Advisory / Consultancy, Research grant / Funding (institution): Merck Sharp & Dohme; Advisory / Consultancy, Research grant / Funding (institution): Merck KGaA; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Advisory / Consultancy, Research grant / Funding (institution): Roche; Advisory / Consultancy, Research grant / Funding (institution): Servier; Research grant / Funding (institution): Amgen; Research grant / Funding (institution): Boehringer Ingelheim. C.S. Fuchs: Advisory / Consultancy: Agios; Advisory / Consultancy: Bain Capital; Advisory / Consultancy: Bayer; Advisory / Consultancy: Celgene; Advisory / Consultancy, Shareholder / Stockholder / Stock options, Officer / Board of Directors, unexercised stock options: CytomX; Advisory / Consultancy: Dicerna; Advisory / Consultancy: Eli Lilly; Advisory / Consultancy, Shareholder / Stockholder / Stock options, unexercised stock options: Entrinsic Health; Advisory / Consultancy: Five Prime Therapeutics; Advisory / Consultancy: Genentech; Advisory / Consultancy: Gilead Sciences; Advisory / Consultancy: KEW; Advisory / Consultancy: Merck; Advisory / Consultancy: Merrimack; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Roche; Advisory / Consultancy: Sanofi; Advisory / Consultancy: Taiho; Advisory / Consultancy: Unum. L. Wyrwicz: Research grant / Funding (institution): MSD; Research grant / Funding (institution): Eisai; Research grant / Funding (institution): BMS; Non-remunerated activity/ies, Patent, royalties, other intellectual property: Cervico; Honoraria (self), Travel / Accommodation / Expenses: Amgen; Honoraria (self), Travel / Accommodation / Expenses: Roche; Advisory / Consultancy: Halozyme; Travel / Accommodation / Expenses: Sanofi; Travel / Accommodation / Expenses: Servier. K-W. Lee: Research grant / Funding (institution): Macrogenics; Research grant / Funding (institution): MSD; Research grant / Funding (institution): Ono Pharmaceutical; Research grant / Funding (institution): Green Cross Corp.; Research grant / Funding (institution): ASLAN Pharmaceuticals; Research grant / Funding (institution): AstraZeneca/MedImmune; Research grant / Funding (institution): Five Prime Therapeutics; Research grant / Funding (institution): LSK BioPharma; Research grant / Funding (institution): Merck KGaA; Research grant / Funding (institution): Array BioPharma; Research grant / Funding (institution): Pharmacyclics; Research grant / Funding (institution): Pfizer. M. Garrido: Research grant / Funding (institution): Novartis. W. Mansoor: Honoraria (self), Speaker Bureau / Expert testimony, Speaker's Bureau - ESMO 2018: Lilly. M.I. Braghiroli: Honoraria (self), Research grant / Funding (institution): Roche; Honoraria (self), Research grant / Funding (institution): MSD; Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy: Merck. E. Goekkurt: Advisory / Consultancy: MSD; Advisory / Consultancy: BMS; Advisory / Consultancy: Roche; Advisory / Consultancy: Sanofi; Advisory / Consultancy: Merck; Travel / Accommodation / Expenses: Servier. J. Chao: Advisory / Consultancy, Research grant / Funding (institution): Merck; Research grant / Funding (institution): Novonco Therapeutics; Advisory / Consultancy: Lilly; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Boston Biomedical; Advisory / Consultancy: FivePrime Therapeutics. Z.A. Wainberg: Advisory / Consultancy: Sirtex Medical; Advisory / Consultancy: Array BioPharma; Advisory / Consultancy, Research grant / Funding (institution): Five Prime Therapeutics; Advisory / Consultancy: Novartis; Advisory / Consultancy: Lilly; Advisory / Consultancy, Research grant / Funding (institution): Merck; Advisory / Consultancy: Merck KGaA; Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy: Aduro Biotech; Advisory / Consultancy, Travel / Accommodation / Expenses: Genentech; Research grant / Funding (institution): Plexxikon; Research grant / Funding (institution): Pfizer. U. Kher: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck & Co., Inc. . S. Shah: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck & Co., Inc. K. Shitara: Honoraria (self): Novartis; Honoraria (self): AbbVie; Honoraria (self): Yakult; Advisory / Consultancy, Research grant / Funding (institution): Astellas Pharma; Advisory / Consultancy, Research grant / Funding (institution): Lilly; Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy: Takeda; Advisory / Consultancy: Pfizer; Advisory / Consultancy, Research grant / Funding (institution): Ono Pharmaceutical; Advisory / Consultancy: MSD; Research grant / Funding (institution): Dainippon Sumitomo Pharma; Research grant / Funding (institution): Daiichi Sankyo; Research grant / Funding (institution): Taiho Pharmaceutical; Research grant / Funding (institution): Chugai Pharma; Research grant / Funding (institution): MSD; Research grant / Funding (institution): MediScience. All other authors have declared no conflicts of interest.